Extraction of Lycopene from Gac Fruit (Momordica cochinchinensis Spreng) and Preparation of Nanolycopene - Oanh, Ho Thi; Nhung, Hac Thi; Tuyen, Nguyen Duc; Kim Van, Lai Thi; Trung, Trinh Hien; Ha, Hoang Mai (Vietnam Journal of Chemistry, 2017)
In this work, we extracted high purity lycopene from dried Gac (Momordica Cochinchinensis) aril using organic solvents. We also succeeded in the preparation of nanolycopene. The effect of temperature on the drying of Gac aril and suitable solvents on the extraction of lycopene has been investigated. The results showed that the suitable drying temperature for Gac aril was 60-70 oC. The suitable solvents for lycopene extraction were dichloromethane or chloroform. The lycopene content in dried Gac aril is about 0.28-0.46 %. Nanolycopene was prepared successfully by freeze-dried method, with relatively small particles size of 40-60 nm. Nanolycopene is relatively stable in the inert environment in the presence of antioxidants such as butylated hydroxytoluene (BHT). Keywords. Momordica cochinchinensis Spreng, Gac Fruit, lycopene, nanolycopene, extraction